2020 IEEE International Conference on Cloud Computing in Emerging Markets (CCEM) 2020
DOI: 10.1109/ccem50674.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

Machine Translation of English Language to Mizo Language

Abstract: The communication between different regional languages is always inevitable fact which requires a lot of effort to make meaningful in terms of technology. The machine translation methods have been endeavoured to fill this impediment. The Neural Machine Translation is one of the efforts which recently gained a remarkable enhancement in the matter of human judgement over the conventional approaches like phrasebased machine translation and statistical machine translation. Thus, the advances of neural machine tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our 2020), the numerous results on the largely South-and Central American languages from the first AmericasNLP conference (Mager et al, 2021), and the Inuktitut language of Canada (Joanis et al, 2020). Datasets for lower-resourced languages of India have also sprung up, including the 13-language PMIndia , and datasets focused on languages of the Northeast like Mizo (Thihlum et al, 2020), Khasi (Laskar et al, 2021) and Assamese (Laskar et al, 2020). Finally, a variety of such datasets and models are available for public use on HuggingFace 10 or Zenodo 11 .…”
Section: Related Workmentioning
confidence: 99%
“…Our 2020), the numerous results on the largely South-and Central American languages from the first AmericasNLP conference (Mager et al, 2021), and the Inuktitut language of Canada (Joanis et al, 2020). Datasets for lower-resourced languages of India have also sprung up, including the 13-language PMIndia , and datasets focused on languages of the Northeast like Mizo (Thihlum et al, 2020), Khasi (Laskar et al, 2021) and Assamese (Laskar et al, 2020). Finally, a variety of such datasets and models are available for public use on HuggingFace 10 or Zenodo 11 .…”
Section: Related Workmentioning
confidence: 99%
“…The author reported that the MT system prediction is reasonable based on fluency but worse on accuracy. [7] conducted a study to evaluate the English to Mizo NMT system on several test datasets from different domains. [26] conducted a study on English to Mizo MT systems (SMT and NMT) on a training dataset collected from various online sources.…”
Section: Related Workmentioning
confidence: 99%
“…Mizo is a Kuki-chin language, a branch of the Sino-Tibetan language, and belongs to the Tibeto-Burman family. The word order in English and Mizo is different; English follows SVO (Subject-Verb-Object), and Mizo follows OSV (Object-Subject-Verb); however, Mizo sometimes follows SVO like English [7]. Furthermore, the second person pronoun "you" is used in English to represent both the singular and plural, whereas the Mizo language has unique phrases for this (for singular "I" and plural "in").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar method was used for English-Hindi [41], and this method was able to generate better results compared to UNMT. A comparison of results was performed on the Mizo VisualGenome dataset [31] with Transformer, BiLSTM, and PBSMT models [35,57,68], where the transformer outperforms the other models. However, it was observed that NMT-based models generate a poor-quality translation for longer sentences.…”
Section: Multimodal Translation On Indian Languagesmentioning
confidence: 99%